The business of American theatre - Grange, William, 1947- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
The Business of American Theatre is a research guide to the history of producing theatre in the United States. Covering a wide range of subjects, the book explores how traditions of investment, marketing, labor union contracts, advertising, leasing arrangements, ticket scalping, zoning ordinances, royalties, and numerous other financial transactions have influenced the art of theatre for the past three centuries. Yet the book is not a dry reiteration of hits and flops, bankruptcies and bamboozles.Nor does it cover "everything about it that's appealing, everything the traffic will allow" (as Irving Berlin did in the song "There's No Business Like Show Business"). It is instead a highly readable resource for anyone interested in how money, and how much money, is critical to the art and artists of theatre. Many of those artists make appearances in the book: Richard Rodgers and his keen eye for investment, Jacob Shubert and his construction of "the bridge of thighs" for his showgirls at the Winter Garden, the significance of the Disney Souvenir Shop near the Lyceum Theatre on Broadway, and the difference between a Broadway showlosing millions of dollars or making billions in one night. Consider this book a go-to resource for readers, students, and scholars of the theatre business.
OCLC-licensed vendor bibliographic record.
Keywords: PERFORMING ARTS / Business Aspects; PERFORMING ARTS / Theater / Broadway & Musical Revue; BUSINESS & ECONOMICS / General; Theater management -- United States -- History; Theater -- Production and direction -- United States -- History; Theater -- United States -- Finance